114k views
0 votes
+43-(-35)=___

Fill in the blanks

User Bodo
by
4.9k points

2 Answers

3 votes
You would first want to get rid of the double negative making the problem
43+35=__
After that just add
43+35= 78
So 78 will be your final answer
User BeeGee
by
5.8k points
4 votes

Here we have first number as positive 43 and the second number is (-35)

so we have to subtract here 43 and (-35)

We will use the following property here:


a-(-b) =a+b

So that means the two negatives will make positive sign,


43-(-35) =43+35

On adding 43 and 35 , we will get 78

Answer: +43-(-35)=78

User Saeed Masoumi
by
5.6k points